2012
DOI: 10.1111/j.1365-2834.2012.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of self-ratings on managerial competencies, research capability, time management, executive power, workload and work stress among nurse administrators

Abstract: The findings inform leaders of hospitals where NAs need to develop additional competencies concerning the type of training NAs need to function proficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 24 publications
2
50
0
1
Order By: Relevance
“…International studies examining PHC and hospital management teams found competency gaps in planning and priority setting, which have negative consequences for health service delivery (7, 25, 43, 48). Studies in LMICs note that planning and priority setting is a skill confined to lists of activities rather than coordinated processes with measurable outcomes and procedures for monitoring performance of PHC clinics (7, 49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International studies examining PHC and hospital management teams found competency gaps in planning and priority setting, which have negative consequences for health service delivery (7, 25, 43, 48). Studies in LMICs note that planning and priority setting is a skill confined to lists of activities rather than coordinated processes with measurable outcomes and procedures for monitoring performance of PHC clinics (7, 49).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches include personality and psychometric tests (17, 18, 24), self-ratings (25), formal examinations (26), case studies (27), and vignettes of management challenges (28). In South Africa, personality and psychometric tests using different types of Likert scales are used to measure competencies of executive managers (17, 18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the nurse manager does not recognize these issues as an essential part of the job, or a nurse manager recognizes a knowledge gap related to these issues, she/he should have the option to have more education and training in nursing management [4,5]. Nurse managers usually have a high-level of education so they should make more efforts to utilize it in their management work and update their expertise in management as well.…”
Section: Discussionmentioning
confidence: 99%
“…These changes pose challenges for delivering high-quality patient care and ensuring a good standard of customer orientation. The adequacy of the managerial skills of nurse managers is an essential issue in responding to these questions [4].…”
Section: Introductionmentioning
confidence: 99%